Early Macrophage Infiltration and Sustained Inflammation in Kidneys From Deceased Donors Are Associated With Long‐Term Renal Function. Issue 3 (15th September 2016) - Guillén‐Gómez, E.; Dasilva, I.; Silva, I.; Arce, Y.; Facundo, C.; Ars, E.; Breda, A.; Ortiz, A.; Guirado, L.; Ballarín, J. A.; Díaz‐Encarnación, M. M.
Abstract : Kidney transplants from living donors (LDs) have a better outcome than those from deceased donors (DDs). Different factors have been suggested to justify the different outcome. In this study, we analyzed the infiltration and phenotype of monocytes/macrophages and the expression of inflammatory and fibrotic markers in renal biopsy specimens from 94 kidney recipients (60 DDs and 34 LDs) at baseline and 4 months after transplantation. We evaluated their association with medium‐ and long‐term renal function. At baseline, inflammatory gene expression was higher in DDs than in LDs. These results were confirmed by the high number of CD68‐positive cells in DD kidneys, which correlated negatively with long‐term renal function. Expression of the fibrotic markers vimentin, fibronectin, and α–smooth muscle actin was more elevated in biopsy specimens from DDs at 4 months than in those from LDs. Gene expression of inflammatory and fibrotic markers at 4 months and difference between 4 months and baseline correlated negatively with medium‐ and long‐term renal function in DDs. Multivariate analysis point to transforming growth factor‐β1 as the best predictor of long‐term renal function in DDs. We conclude that early macrophage infiltration, sustained inflammation, and transforming growth factor‐β1 expression, at least for the first 4 months, contribute significantly to the difference in DD and LD transplant outcome. Abstract : Early and preimplantation inflammation of deceased donor renal grafts is associated with poor medium‐ and long‐term function.